Critical theory and the anthropology of heritage landscapes - Baird, Melissa F.; Shackel, Paul A. (Cultural heritage studies, 2017)
In this book, Baird argues that heritage landscapes must be considered within their socio-political and historical contexts, focusing on the logic that underlies negotiations rather than individuals.
Keywords: Landscape protection; Historic preservation; Historic sites; National parks and reserves; perinnemaisema; maisemansuojelu; kulttuurihistorialliset suojelukohteet; kansallispuistot; alkuperäiskansat; aboriginaalit; kotiseutuoikeus; kulttuuriperintö; traditionslandskap; landskapsskydd; kulturhistoriska skyddsobjekt; nationalparker; urbefolkningar; aboriginer; hembygdsrätt; kulturarv; Australia; Altai; Alaska; Australien; Altaj